Importance of Bleeding Disorder in the Management of Dental Patients (Dhaka Shishu (Children) Hospital Journal, 2021)
Dental practitioners must be aware of the importance of bleeding disorders in the management of dental patients. Initial recognition of such bleeding disorders, knowledge of their possible systemic causes and clear idea in the management of the cases for dental treatment or when to refer those cases to secondary care, plays a crucial and important role in reducing potential complications and negative side effects. The purpose of this article is to review common bleeding disorders, complications and their management that dentists might find in their daily dental practice.DS (Child) H J 2018; 34(1) : 41-47